SEASONAL FLUCTUATIONS AND EXTENT OF LOSSES OF BRINJAL SHOOT AND FRUIT BORER - SINGH, SARVENDRA; Kumar, AKHILESH; AWASTHI, B.K. (Annals of Agricultural Research, 2014)
The incidence and intensity of brinjal shoot and fruit borer was studied in relation to different abiotic factors at Kanpur conditions. The period of incidence occurred from2nd week of September to 2nd week of October when 76.66-93.33 per cent plants were found to be infested with an intensity of 1.16-2.90 damaged shoots per plant. Maximum intensity (2.90 shoots/plant) was recorded in the 4th week of September, when the incidence was also maximum (93.33 per cent) and average temperature was 28o C with 75 per cent relative humidity. The initiation of shoot and fruit borer damage on fruits was recorded in the first week of October. Initially the infestation and intensity were high with 1.66 per fruit and 66.66 per cent damage fruit, respectively. The average temperature above 21oC and relative humidity above 65 per cent were found to be more favourable for the pest multiplication. The average losses due to shoot and fruit borer on brinjal fruits were calculated as 13.30 per cent, out of which only 4.83 per cent were found to be totally unconsumable losses.